Comunidades ribeirinhas, engenheiros e conservação da floresta: construção participativa do espaço tecnológico em empreendimentos econômicos solidários na Amazônia - Candido, Silvio Eduardo Alvarez (2010)
The purpose of this research is to analyse the participatory construction of the technological space of a solidarity economy organization of production and commercialization of Brazil nuts integrated by inhabitants of riverside communities of the Lower Madeira River, in Rondônia. The restore of household extractive economies is one of the proposals of forest peoples social movements to match life quality improvement and environmental conservation. This opposes to the hegemonic model of development of the Amazon Rainforest region, based on technocratic state intervention, which is responsible for the harsh social and environmental crises that hit the region and which has in the expel of.traditional forest people from their home lands one of the most perverse effects. New extractive economies have two features that also oppose the early rubber tapping period. Firstly it is based on democratic work relations, what suggest a connection with solidarity economy movement. On the other hand, it purposes it should incorporate new technologies which would radically improve productive forces, calling for integration with social technology movement. Exploring the existing synergies of these counter-hegemonic movements, the dissertation aims to demonstrate that engineers, technologists and other professionals involved with technological development may assume an important role to merge community strengthen and forest conservation. To do so, the methodology developed by Herrera (1981), alluding to the generation and technology for rural areas, is taken as an important reference. The scope of this method is adapted to be applicable to a solidarity economy organization including extractivists of the Lower Madeira River producing and commercializing Brazil nuts. Recognizing the social character of rational systems, the methodology demands qualified participation of the workers and results in the technological space of the organization, agreed upon the associated producers and the professionals aiming to support them. The experience of the adapted method proved to be effective, pointing out that real engagement of specialists with social transformation demands the capacity of dialoguing with groups which and usually considered irrelevant in the technological development process.